Komunikasi Persuasif Pengasuh Pesantren Dalam Pembinaan Kemandirian Santri Di Bidang Pertanian (Studi Kualitatif Di Pondok Pesantren Mutiara Al Qur'an Selangit) - Bintang Fajri; Anis Endang SM; Maryaningsih Maryaningsih (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study was motivated by the importance of independence education in Islamic boarding schools, which focuses not only on academic and religious aspects but also on practical life skills. The Mutiara Al Qur'an Selangit Islamic Boarding School integrates agricultural activities as a medium for character building among students. However, the success of this development is greatly influenced by the communication process carried out by the caregivers toward the students. Therefore, this study aims to analyze the stages of persuasive communication in shaping students’ independence through agricultural activities. This study used a qualitative approach with a descriptive method. The research subjects consisted of the head of the foundation, boarding school caregivers, and students. Data were collected through in-depth interviews, participatory observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, and its validity was tested using source and method triangulation techniques. The results of the study indicate that persuasive communication occurs through five stages: informing, explaining, convincing, persuading, and obtaining commitment. At the informing stage, students are introduced to the objectives of agricultural activities as independence education. The explaining stage is carried out through direct practice and two-way interaction. The convincing stage is built through the example set by the caregivers and field experience. The persuading stage is conducted through a personal and motivational approach. The commitment stage is demonstrated by the emergence of initiative, responsibility, and active participation of students in agricultural activities. The obstacles found include the absence of written modules, time constraints, and differences in students’ readiness levels. The conclusion shows that persuasive communication is effective in shaping students’ independence, but its sustainability requires systematic reinforcement through a structured curriculum, activity documentation, and periodic evaluation.